4x-6y=12

The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.

y=mx+b

Subtract 4x from both sides of the equation.

-6y=12-4x

Divide each term by -6 and simplify.

Divide each term in -6y=12-4x by -6.

-6y-6=12-6+-4x-6

Cancel the common factor of -6.

Cancel the common factor.

-6y-6=12-6+-4x-6

Divide y by 1.

y=12-6+-4x-6

y=12-6+-4x-6

Simplify 12-6+-4x-6.

Simplify each term.

Divide 12 by -6.

y=-2+-4x-6

Cancel the common factor of -4 and -6.

Factor -2 out of -4x.

y=-2+-2(2x)-6

Cancel the common factors.

Factor -2 out of -6.

y=-2+-2(2x)-2(3)

Cancel the common factor.

y=-2+-2(2x)-2⋅3

Rewrite the expression.

y=-2+2×3

y=-2+2×3

y=-2+2×3

y=-2+2×3

Reorder -2 and 2×3.

y=2×3-2

y=2×3-2

y=2×3-2

Rewrite in slope-intercept form.

y=23x-2

y=23x-2

Find the values of m and b using the form y=mx+b.

m=23

b=-2

The slope of the line is the value of m, and the y-intercept is the value of b.

Slope: 23

y-intercept: -2

Slope: 23

y-intercept: -2

Find the Slope and Y-Intercept 4x-6y=12